Grain size data sheet: Weiße Elster overbank silt-clay deposition (SC40 core, transect Salsitz) - Helen Ballasus; Christoph Zielhofer; Hans von Suchodoletz; Birgit Schneider (PANGAEA, 2021)
We determined grain size distributions of Holocene fluvial sediments from a recovered drilling core from the Weiße Elster floodplain. We left the 2 mm sieved samples (10 g) in 50 ml 35-% hydrogen peroxide (H2O2) overnight and heated them during the next day to remove organic matter. Subsequently, we dispersed the samples using a 10 ml 0.4 N sodium pyrophosphate solution (Na4P2O7) and ultrasonic treatment for 45 minutes. We conducted the grain size analysis of the sand fraction by means of the dry-sieving technique (2000–630 μm: coarse sand, 630–200 μm: medium sand, 200–125 μm: fine sand, 125–63 μm: finest sand). The finer fractions (63–20 μm: coarse silt, 20–6.3 μm: medium silt, 6.3–2.0 μm: fine silt, 2.0–0.6 μm: coarse clay, 0.6–0.2 μm: medium clay and <0.2 μm: fine clay) were measured by X-ray granulometry (XRG) using a SediGraph III 5120 (Micromeritics).